Konfigurasi Voucer Internet dengan Mikhmon Server dan Mikrotik Routerboard Pada Jaringan Komputer Institut Teknologi dan Bisnis Indonesia (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
MikroTik Hotspot Monitor, or abbreviated as Mikhmon, is a Routerboard device management application, such as MikroTik, that it can be controlled from the same network or from a different internet connection. Mikhmon can be accessed via Personal Computer, Hangphone, or website applications, making it easier for admins to manage MikroTik hotspots from various devices as long as they are connected to the internet. Mikhmon is an alternative to RouterOS, or WinBox, which has several features and functions that are considered simpler, and the appearance can be customized using the template provided. Based on this research several conclusions can be using the Mikhmon server can save the load on the routerboard, the use of wireless networks is very useful in terms of convenience in configuring each user manager on the routerboard and easy and stable management.